2006
DOI: 10.1038/sj.bmt.1705319
|View full text |Cite
|
Sign up to set email alerts
|

Donor methylenetetrahydrofolate reductase genotype is associated with graft-versus-host disease in hematopoietic stem cell transplant patients treated with methotrexate

Abstract: Methotrexate (MTX), used as a graft-versus-host disease (GvHD) prophylactic agent in hematopoietic stem cell transplantation (HSCT), exerts its effect via folate cycle inhibition. A critical enzyme involved in folate metabolism is 5,10-methylenetetrahydrofolate reductase (MTHFR). We examined the association of a single nucleotide polymorphism (SNP) at position 677 in the MTHFR gene on GvHD outcomes in allogeneic HSCT patients administered MTX. MTHFR genotyping was performed by polymerase chain reaction-restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 25 publications
0
31
1
Order By: Relevance
“…11 Other studies have also examined SNPs to predict the onset of GVHD, but not their response to steroid therapy or development of SR aGVHD. [12][13][14][15] Given that clinical outcome in SR aGVHD patients is dismal, it is a clinically relevant question if there is a way to predict SR aGVHD even before proceeding to HCT. There might be a chance to select the donor based on SNP information in order to choose the donor with the lowest probability of HCT-related complications in the recipient.…”
Section: Introductionmentioning
confidence: 99%
“…11 Other studies have also examined SNPs to predict the onset of GVHD, but not their response to steroid therapy or development of SR aGVHD. [12][13][14][15] Given that clinical outcome in SR aGVHD patients is dismal, it is a clinically relevant question if there is a way to predict SR aGVHD even before proceeding to HCT. There might be a chance to select the donor based on SNP information in order to choose the donor with the lowest probability of HCT-related complications in the recipient.…”
Section: Introductionmentioning
confidence: 99%
“…26 In addition, another study demonstrated that MTHFR 677CT and TT genotypes in HLA-matched related donors are associated with a decreased risk of GVHD. 27 Recently, an analysis of the impact of donor and recipient MTHFR polymorphisms demonstrated not only differential effects of MTHFR polymorphisms on outcomes but also varying effects in response to FA administration. FA administration, however, was based on the treating physician's discretion, making it difficult to reach definitive conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Two SNPs in the MTHFR gene, 677T/C and T1298 A/C, have been shown to alter its enzymatic activity. A study by Murphy et al 45 identified an association between donor MTHFR SNP 677T* and a decreased incidence of both aGVHD and cGVHD. Later studies also reported an association between recipient MTHFR SNP 677T* and a decreased risk of aGVHD.…”
Section: Candidate Gene Studiesmentioning
confidence: 99%